“Ein beschränkter Verstandesmensch ohne Einbildungskraft” - Anmerkungen zu Friedrich Schillers Urteil über Alexander von Humboldt - Schwarz, Ingo (HiN - Alexander von Humboldt in the Net. International Review for Humboldt Studies, 2003)
Abstract In a letter dated August 6, 1797 to his friend Christian Gottfried Körner, Friedrich Schiller characterized Alexander von Humboldt as a person of limited imagination, who, in spite of his numerous activities, would never be able to achieve greatness in his scientific pursuits. Yet, only in 1849 did Humboldt learn of Schiller’s opinion from the published correspondence between Schiller and Körner. Nonetheless, Humboldt declared that this basically unjust characterization of himself by Schiller would never prevent him from admiring the great German playwright and poet; moreover, Humboldt looked for comfort in a similarly harsh opinion of Johann Gottfried Herder also expressed by Schiller. In the end, Humboldt could barely conceal his feelings of disappointment regarding Schiller’s opinion, especially because Humboldt had considered Schiller to be his friend.